Analisis Program Usaha Ekonomi Produktif Kecamatan Anggrek Kabupaten Gorontalo Utara - Fatria Olii; Irina Popoi; Agil Bahsoan (Universitas Negeri Gorontalo, 2021)
The purpose of this study were to find out (1) the productive economic business program; (2) contributing factors of the productive economy and business program by Bakti Muda Youth Organization in Ibarat Anggrek Village, North Gorontalo. The administrators, members, and community leaders served as the subjects of this qualitative research. Further, the data collection process encompassed interviews, observation, and documentation. The techniques used in data analysis were data reduction, data display, and conclusion. Moreover, the validity of the data was examined using the source and method triangulation. The results showed: (1) the productive economic business program by the Bakti Muda youth Organization included awareness, planning, implementation, and evaluation. The awareness stage involved discussion/sharing, open access to information, and outreach. Meanwhile, the planning stages were identifying needs and planning. The implementations consisted of training, member business implementation, and assistance. The evaluation and development were related to the development of business activites with the exhibition and the Lam Alif Community. Youth organizations handled the facilitator, motivator, technical, and promotion activites in empowering UEP youth. (2) Supporting factors comprised the existence of capital assistance loan facilities, support from various parties, and the number of youth networking partners. Lastly, the inhibiting factors encompassed the consistency of members who do not want to be involved in the development, capital turnover due to the busy schedule of each board and member.